2015
DOI: 10.3109/1354750x.2015.1061598
|View full text |Cite
|
Sign up to set email alerts
|

Urine survivin, E-cadherin and matrix metalloproteinases as novel biomarkers in children with chronic kidney disease

Abstract: The observed parameter changes indicate apoptosis, tissue remodeling and fibrosis in CKD children. Urine survivin may become a new biomarker of kidney-specific EMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…[ 30 , 50 ] Urinary TIMP-1, -2 excretions were reported to be increased in patients with CKD. [ 22 , 51 ] In our study, all patients showed elevated urinary TIMP-1, -2 excretions. In children with SRNS, urinary TIMP-1/Cr ratio was significantly higher than that in children with SDNS.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[ 30 , 50 ] Urinary TIMP-1, -2 excretions were reported to be increased in patients with CKD. [ 22 , 51 ] In our study, all patients showed elevated urinary TIMP-1, -2 excretions. In children with SRNS, urinary TIMP-1/Cr ratio was significantly higher than that in children with SDNS.…”
Section: Discussionsupporting
confidence: 59%
“…[ 21 ] Recent studies showed positive correlation between urinary TGF-beta excretion and urinary excretions of MMP-2 and -9 that confirm their profibrotic action. [ 22 ] Experimental data and human studies demonstrated that increased MMPs glomerular expression correlates positively with severity of glomerular damage and progression of kidney disease. [ 23 26 ] Recent studies in patients with chronic kidney disease (CKD), diabetic nephropathy, and after kidney transplantation demonstrated that higher serum levels and/or urinary excretions of MMPs and TIMPs might be biomarkers for an early stage of RF or its progression.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion signaling mediated by integrins were shown to induce EMT in association with TGF-b receptor signaling. MMP-2/9 play critical roles in tumor cell invasion and metastasis by hydrolyzing extracellular matrix [46]. In the present study, inhibition of metastasis is achieved as the OCT-modified daunorubicin plus dihydroartemisinin liposomes increase cell-cell adhesion by enhancing E-cadherin activity and markedly downregulate TGF-b1, VEGF, a5b1-integrin, and MMP-2/9 in breast cancer cells ( Figure 6).…”
Section: Discussionmentioning
confidence: 56%
“…They have even warned about targeting this molecule in cancer therapy because of its harmful effects on tubular integrity [ 17 ]. Musiał et al studying chronic kidney disease (CKD) in children have observed increased amounts of survivin in patients' urine samples which was not in concordance with its serum level, so they suggested that this molecule is expressed in renal tissue probably as a protective factor against progressive damage and recommended survivin as a diagnostic maker in CKD follow-up; however, it could be presumed that survivin has been released and shed from tubules into the urine flow because of tissue destruction as a consequence of CKD pathogenesis [ 18 ].…”
Section: Survivin In Transplantationmentioning
confidence: 99%